Feasibility Analysis of Siamese Orange Farming Business in Banyuwangi - Wanto, Hary (Economic and Business Horizon, 2022)
Tropical countries have priceless natural resources and are very suitable places to grow various kinds of plants, one of which is fruit plants. One of the favorite fruits in Indonesia that thrives is citrus fruit. The prospect of citrus agribusiness in Indonesia is quite good because of the potential for extensive production land. farmers will plant and develop tangerine farming if it is financially profitable. the formulation of the problem includes questions regarding the amount of revenue obtained from Siamese Orange farming in Tegalsari village. Revenue is an important indicator to evaluate the income potential of these farming activities. the question of the amount of profit generated from tangerine farming in the village. This research method was carried out in Tegalsari village, Tegalsari sub-district, Banyuwangi regency, which was chosen deliberately because most of the population earns a living as a chayote farmer. data collection methods using interviews and questionnaires are expected to provide an in-depth understanding of the practice of chayote farming in Tegalsari village. In such a situation farmers are faced with various circumstances. To cover the physical weaknesses of farmers utilize labor in the family and hired labor. The results of research and analysis of citrus farming in Tegalsari village, Tegalsari District, Banyuwangi Regency provide a clear picture of the financial performance and feasibility of the project over a ten-year period.